Pembuatan Career Development Tools (CDT) untuk Departemen Human Resources (HR) Personalia dan Payroll sebagai Pelengkap dari Career Development System (CDS) di PT. X - The, Theisca Doris; Anne Y A, Debora (Jurnal Titra, 2013)
PT. X has already own Career Development System (CDS) as one of the guidelines for employees to develop in incumbent positions, but the use of CDS is not maximal, because CDS is too general and less describe about real job of the employee. Therefore, Career Development Tools (CDT) was invented, which is CDT has three outputs, development plan, evaluation form, and career path. As a first step, CDT is made for HR Department Personalia and Payroll. CDT helps employee to develop with guideline based on real job daily activities (development plan), helps evaluate employee (evaluation form), and provide general career lattice for employee (career path).